Culturas, memórias e outras histórias: processos e disputas na e pela cidade de Nova Ponte/MG (1960-2013) - Inácio, Juliana Lemes (2014)
This thesis discusses social process of memories elaboration concerning transformations experienced in Nova Ponte, MG. I sought to understand the ways how workers mean changes and continuities in their ways of living. I analyze the ways how the subjects dealt with the arrival process of a hydroelectric plant in Nova Ponte City, causing the city expropriation and a new city construction. The hydroelectric plant was implanted for Cemig. Its construction began in 1987 and its inauguration took place in 1994, along with the new city delivery . I sought to reflect about the ways how workers instituted their territories in the city before the arrival of the company, their ways of living and working, bringing the life harshness, the multiples employment relationships, but also the leisure time. In this sense, interviewee s narratives brought other histories and a constituted temporality from the 1960s. Treading temporality and culture relatives listed by workers, I could realize the meanings they attach when living in the city that was intersected by Araguari River. The ways they distinguished and recognized themselves in the spaces of the city, as this side and that side of the river, indicate class boundaries in which they were inserted. This study still emerge the workers projected expectations in relation to changes, the fear and insecurity concerning the way their living were been transformed, seeking to understand the convincement strategies created, and the clashes forged in the new city negotiation process. Evidences worked in this research were oral narratives, Cemig s various documents, as reports, books, newsletters, newspaper clippings, photographs, newspaper and minutes of Nova Ponte City Council.